Egypt Economic Monitoring Note, Fall 2012 - Laursen, Thomas; Badr, Karim; Zaki, Chahir (World Bank, Washington, DC, 2017)
Egypt is in a precarious economic situation reflecting a difficult external environment, political uncertainty, and weak economic policies. International reserves have been declining rapidly to a low level, driven by a sizeable current account deficit and large capital outflows. Large spending increases are driving up the fiscal deficit to unsustainable levels, with high real interest rates and weak growth adding to the mounting debt burden. And weak growth is fueling social pressures. Strong financial support from Arab bilateral donors has been holding the country afloat so far, but the leaking cannot continue much longer and the authorities have been forced to seek support from the International Monetary Fund (IMF) and other donors. Egypt is in a precarious economic situation reflecting a difficult external environment, political uncertainty, and weak economic policies. International reserves have been declining rapidly to a low level, driven by a sizeable current account deficit and large capital outflows. Large spending increases are driving up the fiscal deficit to unsustainable levels, with high real interest rates and weak growth adding to the mounting debt burden. And weak growth is fueling social pressures. Strong financial support from Arab bilateral donors has been holding the country afloat so far, but the leaking cannot continue much longer and the authorities have been forced to seek support from the IMF and other donors.